2022
DOI: 10.1002/chem.202104421
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Supramolecular Nanostructures through in Situ Self‐Assembly and Post‐Assembly Modification of a Biocatalytically Constructed Dipeptide Hydrazide**

Abstract: Aqueous self-assembly of short peptides has attracted growing attention for the construction of supramolecular materials for various bioapplications. Herein, we describe how the thermolysin-assisted biocatalytic construction of a dipeptide hydrazide from an N-protected amino acid and an amino acid hydrazide leads to the formation of thermally stable supramolecular hydrogels. In addition, we demonstrate the post-assembly modification of the supramolecular architectures constructed in situ tethering hydrazide gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Among these, the diphenylalanine peptide (L-Phe-L-Phe; FF) is perhaps the most famous and also the core recognition motif of the Alzheimer's β-amyloid peptide [152,153]. Many studies indicated that this peptide and its derivatives can self-assemble into highly ordered nanostructures such as NPs and nanoribbons [154,155], or nanoscale matrices such as hydrogels [15]. In the FF dipeptide system, the main driving force of the structure self-assembly is the hydrophobic interaction and the π-π interaction.…”
Section: Short Peptidesmentioning
confidence: 99%
“…Among these, the diphenylalanine peptide (L-Phe-L-Phe; FF) is perhaps the most famous and also the core recognition motif of the Alzheimer's β-amyloid peptide [152,153]. Many studies indicated that this peptide and its derivatives can self-assemble into highly ordered nanostructures such as NPs and nanoribbons [154,155], or nanoscale matrices such as hydrogels [15]. In the FF dipeptide system, the main driving force of the structure self-assembly is the hydrophobic interaction and the π-π interaction.…”
Section: Short Peptidesmentioning
confidence: 99%